Metal nanotrough embedded colorless polyimide films: transparent conducting electrodes with exceptional flexibility and high conductivity. Issue 17 (19th April 2018) - Moon, Ji-Young; Youn, Doo-Young; Kim, Chanhoon; Lee, Ji-Hyun; Luo, Zhenhao; Kim, Il-Doo
Abstract : We present an inverted-heart shape Ag nanotrough electrode based on the fusion of a CPI substrate and Ag layer-coated CPI nanofibers. Abstract : Reliable performances with a long lifetime are the most important factors of transparent conducting electrodes (TCEs). Here, we report a new synthesis strategy for high-performance TCEs based on the fusion of a polyimide (PI) substrate and silver layer-coated PI nanofibers. Due to the successful fusion of the substrate into the core without immiscibility, the as-synthesized TCEs showed excellent performances (a sheet resistance of 1.33 Ω sq −1 and a total optical transmittance of 88%) even after 100 000 bending cycles at a bending radius of 1.75 mm.